Ethnic Dissent and Empowerment : Economic Migration between Vietnam and Malaysia - Tran, Angie Ngoc (Book collections on Project MUSE., 2021)
"This book focuses on guest workers in Malaysia from five of Vietnam's fity-four ethnic groups: the Kinh (Vietnam's ethnic majority), the Hoa (ethnic Chinese), the Khmer, the Chăm Muslims, and the Hrê. The groups engage in different migration patterns, forms of resistance, and forms of empowerment. The transnational labor brokerage state (LBS) system affects female and male migrants differently, from the dehumanizing recruitment phase, to the precarity of working in Malaysia and the open protest to abuses, to forms of empowerment, including remittances, debt defaults, and stepwise international migration, through which workers migrate to different countries in a stepwise fashion to improve their condition. These guest workers draw on their economic and cultural resources to survive, thrive in the LBS system, or bypass it altogether. They engage in different "third spaces" of dissent. Physical third spaces are not defined in terms of the legal and illegal categories of the law but by the tacit acceptance of the community in which the migrants live and work. Metaphorical third spaces are discourses of dissent, uttered by nonstate competing authorities in order to challenge the state's authority through ironic and subversive mimicries. The findings are based on eight years of research and fieldwork interviews in Vietnam and Malaysia (2008-15), a significant period of change in labor export policies"--